Gambaran Sikap Ibu Tentang Kejadian Stunting Di Masa Pandemi Covid-19 Di Puskesmas Sudiang Makassar - Sitti Hasrah Ibrahim; Hijrawati Hijrawati (Jurnal Mahasiswa Ilmu Kesehatan, 2023)
Description of Mother's Attitudes About Stunting During the COVID-19 Pandemic at the Sudiang Makassar Health Center (supervised by Ayatullah Harun & Hukmiyah Aspar). Stunting is a condition of failure in child growth and development (body and brain growth) caused by malnutrition for a long time. Thus, children who experience this condition tend to be shorter or shorter in body shape than normal children of their age and have delays in thinking. The purpose of this study was to describe the mother's attitude towards stunting during the COVID-19 pandemic at the Sudiang Makassar Health Center. This study used an observational analytic method, namely a descriptive approach, to describe the mother's attitude towards stunting during the COVID-19 pandemic at the Sudiang Makassar Health Center with a total population of all mothers who had babies aged 0-12 months at the Sudiang Makassar Health Center who visited the January 2022, namely 37 people and a total sample of 30 people using the Accidental Sampling technique. The results of this study indicate that the description of the mother's attitude regarding the incidence of stunting during the COVID-19 pandemic at the Sudiang Makassar Health Center with a good attitude was 12 people (40.0%) and a bad attitude was 18 people (60.0%). It can be concluded that the picture of the mother's attitude regarding the incidence of stunting during the COVID-19 pandemic at the Sudiang Makassar Health Center was not good by looking at the results that had been obtained. So it is suggested that there is a need for education by health workers to the community, especially to mothers regarding the impacts or risks that will occur in children who are stunted.